Advances in the Study of Exosomes as Drug Delivery Systems for Bone-Related Diseases - Jiawen Huang; Yang Xu; Yuxuan Wang; Zhiang Su; Tingting Li; Sisi Wu; Yuheng Mao; Shihua Zhang; Xiquan Weng; Yu Yuan (MDPI AG, 2023)
Bone-related diseases are major problems and heavy burdens faced by modern society. Current clinical approaches for the treatment of these pathological conditions often lead to complications and have limited therapeutic efficacy. In this context, the development of nanotherapeutic platforms, such as extracellular vesicles, can improve the relevant therapeutic effects. In particular, exosomes are nano-sized, lipid bilayer extracellular vesicles secreted by many cells in mammals. Due to their innate capacity to transport materials-including proteins, lipids, and genes-among cells, as well as their innate attraction to target cells, they are considered to be a crucial medium for cell communication and are involved in a number of biological processes. Exosomes have been used as drug delivery vehicles in recent bone tissue engineering studies, in order to regulate bone homeostasis. However, the precise workings of the exosome regulatory network in maintaining bone homeostasis and its potential for treating bone injury remain unclear. To provide a fresh perspective for the study of exosomes in drug delivery and bone-related diseases, in this paper, we review recent studies on the roles of exosomes for drug delivery in bone homeostasis and bone-related diseases, as well as the composition and characteristics of exosomes and their regulatory roles in bone homeostasis and bone-related diseases, aiming to provide new ideas for the therapeutic application of exosomes in the treatment of bone-related diseases.